Pemanfaatan Bubuk Andaliman sebagai Bahan Pengawet Alami pada Bakso - Vhierda Windasari Sagala; Usman Pato; Yusmarini Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Meatball is a food product of processed meat. The purpose of this research was to obtain the best concentration of andaliman powder as a natural preservative on the quality and sheef life of meatballs. This research was carried out experimentally by using Completely Randomized Design (CRD) with five treatments and three replications in order to obtain fifteen experiments unit. The treatment in this research were V1 (without andaliman powder), V2 (0.1% andaliman powder), V3 (0.3% andaliman powder), V4 (0.5% andaliman powder), and V5 (0.7% andaliman powder). The parameters observed were moisture, ash, protein and, fat contents, microbial counts and sensory test. The best concentration of andaliman powder was V4, with is moisture content 35.87%, ash 3.38%, protein 9.11%, fat 1.05%, microbial counts 1.51x106. The descriptive sensory test of meatball were dark brown (4.13), taste of andaliman (3.63), flavour of beef and andaliman (3.37), elasticity of little chewy (3.33) and the overall test of sensory liked by panelist (3.56).Keywords: Meatball, beef, andaliman powder concentration